Does Rapid and Sustained Economic Growth Lead to Convergence in Health Resources - Di Liang BM; Donglan Zhang PhD; Jiayan Huang PhD; Stuart Schweitzer PhD (SAGE Publishing, 2016)
China's rapid and sustained economic growth offers an opportunity to ask whether the advantages of growth diffuse throughout an economy, or remain localized in areas where the growth has been the greatest. A critical policy area in China has been the health system, and health inequality has become an issue that has led the government to broaden national health insurance programs. This study investigates whether health system resources and performance have converged over the past 30 years across China's 31 provinces. To examine geographic variation of health system resources and performance at the provincial level, we measure the degree of sigma convergence and beta convergence in indicators of health system resources (structure), health services utilization (process), and outcome. All data are from officially published sources: the China Health Statistics Year Book and the China Statistics Year Book. Sigma convergence is found for resource indicators, whereas it is not observed for either process or outcome indicators, indicating that disparities only narrowed in health system resources. Beta convergence is found in most indicators, except for 2 procedure indicators, reflecting that provinces with poorer resources were catching up. Convergence found in this study probably reflects the mixed outcome of government input, and market forces. Thus, left alone, the equitable distribution of health care resources may not occur naturally during a period of economic growth. Governmental and societal efforts are needed to reduce geographic health variation and promote health equity.